Story Problem for Low-Grade Primary Students: Discourse Analysis - *, Sumarwati; *, Budiyono; Anindyarini, Atikah (Sebelas Maret University, 2016)
Story problem is the type of math problems presented by the media of language and story. This study was done to identify the type of discourse structure of the story problem in mathematics textbooks for low-grade student in primary school. The focus of study is viewed from the number of components and the type of the integration of those components. There are three components in the story problems, namely introduction, events, and question component. Nine mathematics textbooks of 1th, 2nd, and 3rd were taken as sample with three books for each grade. The study result about the number of components composing story problems also shows that most of story problems for primary one, two, and three-grade consist of three components. The others are story problems with only two components by omitting the first component which is the introduction component. Viewed from the components integration type, result shows that story problems components that are combined for primary two and three are the introduction and events components or the events and question components. The integration between introduction component and events component is indicated by the conjunction âandâ, âwhile/whereasâ, and a comma. The integration between events and question component is indicated by the conjunction âifâ. It will all produce complex sentences. The conclusion of this study is that, viewed from their discourse structure, most story problems for primary one and two students are relatively shorter than three, by omitting the setting and character element in introduction. It implies that there is no introduction part to introduce the context or narrative elements whose function is to connect the real world and mathematics.